2020
DOI: 10.1080/03007995.2020.1815001
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics of insulin lispro 200 units/mL users in real world setting in Germany

Abstract: Objective: Insulin lispro 200 U/mL (IL200) is a treatment choice for people with diabetes who have daily mealtime insulin (MTI) requirements of >20 U/day. We report clinical characteristics of real world IL200 users in Germany to understand clinical settings and the type of patients who would benefit from IL200 treatment. Methods: This retrospective database analysis used the patient-level data from "IMS Disease Analyzer" in Germany from February 2015 to June 2016. Clinical and demographic information were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
2
4
1
Order By: Relevance
“…It showed that patients with T1D and T2D who were prescribed IL200 generally presented with poor glycemic control, a high BMI, and diabetes-associated comorbidities and were receiving high doses of insulin at IL200 initiation. This patient profile is aligned with previous observational studies of IL200 in other European countries [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It showed that patients with T1D and T2D who were prescribed IL200 generally presented with poor glycemic control, a high BMI, and diabetes-associated comorbidities and were receiving high doses of insulin at IL200 initiation. This patient profile is aligned with previous observational studies of IL200 in other European countries [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…The largest age group of patients was 18–39 years for those with T1D and 60–69 years for those with T2D. Patients with T1D cannot be compared with other real-world studies of patients receiving IL200, as these mostly or only comprised patients with T2D [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there was a lack of representation of T1DM, younger patients and non-obese patients, therefore concluding IL200 satisfaction and preferences for these groups are limited. However, our sample characteristics match closely to a recent retrospective cohort study of 811 IL200 users [15] which may lend confidence to the generalizability of our study and explain the underrepresentation of certain groups in our sample.…”
Section: Discussionsupporting
confidence: 84%
“…No evidence was found to suggest that any other demographic or clinical characteristic was associated with higher or lower satisfaction for IL200. It is possible that many physicians tend to prescribe IL200 to patients who are obese [15] because of higher insulin requirements of obese patients; however, our study did not support this in terms of differences in patient satisfaction for IL200 for different BMI groups.…”
Section: Discussioncontrasting
confidence: 79%